A phylogenetic evaluation of Panicum sects. Agrostoidea, Megista, Prionitia and Tenera (Panicoideae, Poaceae): Two new genera, Stephostachys and Sorengia - Zuloaga, Fernando Omar (2010)
The taxonomic features of species of Panicum, previously classified in Panicum subg. Agrostoidea and Phanopyrum including sects. Megista, Tenera, Prionitia and Agrostoidea, are reviewed and compared with subg. Panicum and other taxa of Paniceae. All taxa, previously considered in these subgenera and sections, are now included in the new genera Stephostachys and Sorengia, which are based on morphological and molecular characters. Stephostachys includes one species, S. mertensii (Roth) Zuloaga & Morrone, ranging from Mexico to Argentina, while Sorengia comprises seven species, S. anceps (Michx.) Zuloaga & Morrone, S. caricoides (Nees ex Trin.) Zuloaga & Morrone, Sorengia longifolia (Torr.) Zuloaga & Morrone S. petersonii (Hitchc. & Ekman) Zuloaga & Morrone, S. prionitis (Nees) Zuloaga & Morrone, S. stenodes (Griseb.) Zuloaga & Morrone, and S. tenera (Beyr. ex Trin.) Zuloaga & Morrone, distributed from the United States to Bolivia and Brazil. Affinities of the new genera with other genera of Paniceae are discussed. Lectotypes are designated for Panicum caricoides var. glabriusculum Döll, P. caricoides var. pilosum Döll, P. prionitis Nees, P. prionitis var. varium Kuntze, and P. stenodes Griseb.